The Disproportionate Burden of the COVID-19 Pandemic Among Pregnant Black Women. (November 2020) - Gur, Raquel E.; White, Lauren K.; Waller, Rebecca; Barzilay, Ran; Moore, Tyler M.; Kornfield, Sara; Njoroge, Wanjiku F.M.; Duncan, Andrea F.; Chaiyachati, Barbara H.; Parish-Morris, Julia; Maayan, Lawrence; Himes, Megan M; et al.
Abstract: The COVID-19 pandemic has disproportionately impacted the well-being of vulnerable populations in the US, including Black people. The impact on pregnant women is of special concern for the intrauterine and post-natal development of their offspring. We evaluated in an online survey a sample of 913 pregnant women, 216 Black, 571 White, 126 Other, during a 2-week stay-at-home mandate in the Philadelphia region. We applied logistic regression models and analysis of covariance to examine general and pregnancy-specific worries and negative consequences arising from the COVID-19 pandemic, symptoms of anxiety and depression, and resilience. Black pregnant women reported greater likelihood of having their employment negatively impacted, more concerns about a lasting economic burden, and more worries about their prenatal care, birth experience, and post-natal needs. In the full sample, 11.1% of women met screening criteria for anxiety and 9.9% met criteria for depression. Black women were more likely to meet criteria for depression than White women, but this difference was not significant accounting for covariates. Resilience factors including self-reliance and emotion regulation were higher in Black women. Racial disparities related to COVID-19 in pregnant women can advance the understanding of pregnancy related stressors and improve early identification of mental health needs.